Composição e distribuição de crustáceos decápodes associados à pesca do camarão-sete-barbas Xiphopenaeus kroyeri (heller, 1862) no litoral norte do estado de São Paulo - Mantelatto, Fernando L.; Bernardo, Camila H. [UNESP]; Silva, Thiago E. [UNESP]; Bernardes, Verônica P. [UNESP]; Cobo, Valter J.; Fransozo, Adilson [UNESP] (Boletim do Instituto de Pesca, 2016)
The aims of this study were to identify spatially and temporally the composition and diversity of decapod crustaceans caught at fisheries of shrimp Xyphopenaeus kroyeri in Ubatuba bay. Samples were obtained monthly with a shrimping boat from September 1995 to August 1996 at 8 permanent transects. In total were collected 233094 individuals belonging to 85 species. The greatest riches were obtained for Brachyura (49 species) and Anomura (16 species). In the transects IV and V, the highest values of diversity and smaller abundance of shrimp X. kroyeri were found. Regarding the similarity, transects IV and V has low similarity in relation to other points due to its characteristics, such as location in the bay and type of substrate. Studies on the diversity of bycatch of commercially important shrimps are essential for management plans and conservation of renewable natural resources.
Composition and distribution of decapod crustaceans associated by fisheries of seabob shrimp Xiphopenaeus kroyeri (heller, 1862) at the northern coast of São Paulo
Keywords: Biodiversidade; Bycatch; Crustacea; Decapoda; Ubatuba